20. The Histological Structure of Tegal Duck (Anas javanicus) Spleen at Different Age - Nabila Latifa Hafizsha; Hamdani Budiman; Hamny Hamny; Dian Masyitha; Cut Dahlia Iskandar; Ummu Balqis; Muhammad Jalaluddin (Jurnal Medika Veterinaria, 2017)
The aim of the  study was to determine the histological structure of tegal duck (Anas javanicus) spleen according to ages variation. One month, 2 month and 3 months of tegal duck were used as the sample of this study. The spleen of each duck was analyzed by Hematoxylin-Eosin (HE) method, then observed under light microscope. The result of this study performed there were the differences of histological structure of the ducks spleen. The capsule thickness had increased along with increasing age, which was 16.0 ± 1.0 µm; 25.3 ± 2.5 µm; and 29.0 ± 1.0 µm. The boundary between the two pulp in the tegal duck 3 months  old more obvious than 1 month or 2 months old. The diameter of white pulp had increased in the oldest duck. It can be concluded that the development of spleen histological structure was more perfect with the  increasing age of tegal duck.